Caracterización de cepas del virus de la fiebre aftosa emergentes en el cono sur de Sudamérica entre 2000-2011 y su protección por vacunas - Galdo Novo, Sabrina (2018)
Foot-and-mouth disease virus is responsible for one of the most contagious vesicular diseases in cattle and other cloven-hooved animals. The disease constitutes a latent\nthreat for free countries, since viral incursions entail significant economic losses not only because of production shortages, but also due to the closure of commercial markets. The\nArgentine Republic is a country recognized by the World Organization for Animal Health\n(OIE) as free of foot-and-mouth disease without vaccination in the region of latitude 42°\nsouth and free with vaccination at the north of it. The National Service for Agrifood Health\nand Quality (SENASA), being the national official control entity and having been recognized as ?Reference Laboratory for foot-and-mouth disease? by the OIE, has among\nits main activities, the study of foot-and-mouth disease virus in order to contribute to\ndeepen its knowledge. In this context, the characterization of the type O emergencies\nthat occurred sporadically during the years 2000-2011 in areas of the Southern Cone of South America, previoulsy recognized as free of foot and mouth disease with systematic\nvaccination by the OIE, was of utmost importance. This work presents the first study of the variants responsible for the above-mentioned emergencies, which included genetic,\nantigenic and immunogenic characterizations, with particular emphasis on their\nrelationship with the vaccine strain O1/Campos, in use in the region. The impact of\ngenetic and antigenic changes on protection by the vaccine in use was evaluated through\n?in vitro? and ?in vivo? heterologous protection tests. Phylogenetic analysis performed\non the nucleotide sequence of the VP1 coding region; aminoacid changes recorded in the\nP1 precursor; and antigenic analysis based on determination of reactivity profiles with a\npanel of monoclonal antibodies showed that these isolates belong to a single genetic\nlineage, although some genetic and antigenic differences could be observed. When\ncompared with the vaccine strain O1/Campos, field isolates recorded considerable\ngenetic and antigenic differences. Studies of ?in vitro? cross-protection with the vaccine strain O1/Campos gave r1 and expectancy of protection values, from which a satisfactory protective response could be inferred at 79 days post vaccination or after revaccination,\nand even at 30 days post-vaccination in some of the viruses studied. The results of the ?in vitro? tests were confirmed by ?in vivo? assays at 79 days post vaccination and after\nrevaccination, using the viral isolate corresponding to the last outbreak ocurred in 2011 in Paraguay, for challenge. The results of the heterologous protection studies are discussed in view of the different objectives for which they will be analyzed: prophylaxis,\nemergency vaccination and/or incorporation of a new field virus in the antigen/vaccine\nbanks. In this regard, and when a more rapid and specific immune response is needed, as in the case of an emergency, biological behavior tests were performed with the strain\ncorresponding to the virus used for challenge, including yield of antigenic mass and the stability of the viral suspensions after their inactivation, to preliminarly evaluate its\npossible incorporation within the national antigen bank.